Cost estimating and cost control on engineering and construction projects - C.A. Miller (My University, 1980)
The word “Cost Engineering” was coined as an engineering discipline only 2 decades ago. Already it has found common usage in the engineering and construction industry throughout. North America and indeed in Europe and other parts of the world.
Keywords: scale; factors; relationships; utilities; cost; refinements